Flexible hydrophobic ZrN nitride films. (September 2016) - Musil, J.; Zenkin, S.; Kos, Š.; Čerstvý, R.; Haviar, S.
Abstract: This article reports on formation of flexible hydrophobic ZrN films with enhanced resistance to cracking prepared by reactive magnetron sputtering. It is shown that (1) the hydrophobicity of the ZrN films is their intrinsic property and all sputtered ZrN films are hydrophobic and (2) the flexibility of the ZrN films with enhanced resistance to cracking is achieved by an optimization of their mechanical properties only. The flexible ZrN films are typical representatives of carbon-free low-electronegativity metal compounds. Highlights: ZrN films are intrinsically hydrophobic. The enhanced resistance to cracking of the ZrN films is optimized by their mechanical properties. ZrN films are suitable carbon-free hydrophobic coatings in harsh environments.